PACKED RED CELL DENGAN DELTA Hb DAN JUMLAH ERITROSIT ANEMIA PENYAKIT KRONIS (Packed Red Cells with Delta Hb and Erythrocytes in Anemia of Chronic Disease) - Novita Indayanie; Banundari Rachmawati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Anemia chronic disease is the second common cause after iron deficiency anemia with hemoglobin levels below the referencevalue. The pathogenesis of anemia should be determined for treatment. Hematinics and or erythropoietin are other treatments besidestransfusion. The transfusion is started when Hb≤7g/dL. The PRC transfusion of 4ml/kg could increase Hb level by 1 g/dL, or 1 unit andcould increase 3–5% of hematocrit. The objective of this study was to know the correlation of PRC unit with delta Hb and erythrocytesin anemia of chronic disease. The 60 samples examined were from patients of the Kariadi Hospital Semarang suffering from anemia ofchronic disease and who were transfused with PRC from January up to March 2014. The study subjects comprised 28 men (46.7%) and32 women (53.3%), with a mean age of 47 years. The number of PRC given was between one (1) to four (4) units. The mean delta Hbwas 3.48 and the mean delta erythrocytes was about 1.03 (0.1 to 2.3). There was a significant correlation between PRC units and deltaHb (r:0.856, p:0.000), as well as delta erythrocytes (r:0.716, p:0.000). Based on this study, it can be concluded that PRC units have avery strong correlation with delta Hb and as well as with delta erythrocytes in patients suffering from anemia of chronic disease